Multicultural Education According to H.A.R Tilaar and Its Relevance in the Social Life of Cirebon City Society - Budiman Hafid (al-Afkar, Journal For Islamic Studies, 2026)
Cirebon City is one of the cities with a rich history and cultural wealth, facing unique challenges in implementing the concept of multicultural education. Understanding how this concept is relevant to the local community's social life can provide further insights into how education can contribute to fostering inclusive and tolerant attitudes amidst the distinctive cultural diversity in Cirebon. The concept of Multiculturalism, advocated by Tilaar, is hoped to serve as a solution to stabilize security, socio-economic aspects, and social harmony, thereby positively impacting the educational realm and the future of Indonesia's diverse society, commonly referred to as a multicultural community. Multiculturalism can be understood as the diversity or differences between one culture and another. This research aims to comprehend multicultural education in Indonesia, understand multicultural education according to H.A.R Tilaar, and evaluate the relevance of the concept of multicultural education according to H.A.R Tilaar to the social life of the community in Cirebon City. The research method employed is literature research using a qualitative approach and literature study, involving data collection techniques such as observation, interviews, and documentation. The research findings indicate that the concept of multicultural education according to H.A.R Tilaar is highly relevant to the social conditions of Cirebon City. This concept encourages the community to fulfill their rights and responsibilities as citizens by emphasizing mutual respect for differences. The implementation of multicultural education is expected to make a positive contribution to the stability of security, socio-economic aspects, and social harmony in Cirebon City, while also shaping inclusive and tolerant attitudes in the face of the unique cultural diversity in the region.